IZAPA'S INDUSTRIAL HINTERLAND: THE EASTERN SOCONUSCO MANGROVE ZONE DURING ARCHAIC AND FORMATIVE TIMES. Issue 2 (20th December 2018) - Neff, Hector; Burger, Paul H.; Culleton, Brendan J.; Kennett, Douglas J.; Jones, John G.
Abstract: Archaeological survey and excavations in the mangrove-estuary zone south of Izapa have generated an understanding of how the environment and human exploitation patterns changed during the Archaic and Formative periods. Archaic-period archaeological remains are not present, but the sedimentary record shows that Archaic people were clearing the coastal-plain forest for agricultural purposes. This activity augmented delivery of sediments to the littoral zone, which expanded the mangrove forest and created a productive environment that could be colonized by Early Formative villagers by around 1600 calb.c. Population growth during the Early Formative created conditions that favored emergence of specialized pyro-industries, especially salt production, by around 1000 calb.c. Production intensity increased thereafter, especially during the Late Formative period, coincident with the apogee of Izapa. Salt production became more episodic during the Terminal Formative period, when interior populations were declining to a nadir after cala.d. 250.